An Analysis Regarding the Prognostic Significance of MAVS and Its Underlying Biological Mechanism in Ovarian Cancer - Chen, Lifeng; Hou, Jing; You, Bingbing; Song, Feifei; Tu, Xinyi; Cheng, Xiaodong (Frontiers in Cell and Developmental Biology, 2021)
Abstract This study evaluates the value of MAVS expression as a potential diagnostic biomarker and therapeutic target for Ovarian Cancer (OC), also analyzes underlying biological mechanism in this pathology. Firstly, the association between the MAVS expression determined by IHC and clinic characteristics was systematically investigated. Overexpression of MAVS is associated with advanced clinical factors and poor survival of OC patients. Secondly, bioinformatics analysis including gene expression, mutation analysis, GSVA, GSEA and WGCNA analysis was performed to evaluate the potential biological functions of MAVS in OC. The results showed that MAVS probably plays a critical role in immune cell infiltration. Then CIBERSORT was applied to assess the infiltration of immune cells in OC. CD8+ T cells, γδT cells and eosinophils had significantly negative correlation with MAVS expression. Finally, sensitivity analysis found that patients with high MAVS expression were predicted significantly less responsive to cisplatin and paclitaxel. In conclusion, these findings suggest that MAVS influences biological behavior by regulating immune respond, which can be used as a predictive marker for poor prognosis in OC.